2019
DOI: 10.1111/bju.14680
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram for predicting the likelihood of postoperative surgical complications in patients treated with partial nephrectomy: a prospective multicentre observational study (the RECORd 2 project)

Abstract: nomogram for predicting the risk of postoperative surgical complications. At decision curve analysis, the nomogram led to superior outcomes for any decision associated with a threshold probability of >5%. ConclusionSeveral clinical predictors have been associated with postoperative surgical complications after PN. We used this information to develop and internally validate a nomogram to predict such risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 31 publications
(44 reference statements)
2
11
0
1
Order By: Relevance
“…With regard to the clinical implications of these findings, and specifically the role of the nephrometry score in predicting postoperative outcomes, the receiver-operating characteristic curves demonstrated that both the 2D and the 3D nephrometry score were correlated with overall and major complications (AUCs calculated with 3D VMs ranging from 0.67 to 0.84), confirming the findings in the literature [29,30]. Nephrometry category, as assessed by the two different imaging tools, was also considered in order to evaluate whether the 2D-or 3D-based category was more closely related to postoperative outcomes.…”
Section: Discussionsupporting
confidence: 82%
“…With regard to the clinical implications of these findings, and specifically the role of the nephrometry score in predicting postoperative outcomes, the receiver-operating characteristic curves demonstrated that both the 2D and the 3D nephrometry score were correlated with overall and major complications (AUCs calculated with 3D VMs ranging from 0.67 to 0.84), confirming the findings in the literature [29,30]. Nephrometry category, as assessed by the two different imaging tools, was also considered in order to evaluate whether the 2D-or 3D-based category was more closely related to postoperative outcomes.…”
Section: Discussionsupporting
confidence: 82%
“…The Italian REgistry of COnservative and Radical surgery for cortical renal tumor Disease (RECORd 2 Project) is a prospective, observational project promoted by the Italian Society of Urology whose collection criteria were previously described [17]. Institutional Review Board approval was obtained for data sharing through the different centers.…”
Section: Methodsmentioning
confidence: 99%
“…years paved the way for the gradually increased employment of minimally invasive approaches, first with the advent of laparoscopy and then with robotics, progressively minimizing the impact and invasiveness of surgical procedures [7][8][9].…”
mentioning
confidence: 99%